Downregulation of Endogenous Hydrogen Sulfide Pathway Is Involved in Mitochondrion-Related Endothelial Cell Apoptosis Induced by High Salt. (11th May 2015) - Zong, Yanfang; Huang, Yaqian; Chen, Siyao; Zhu, Mingzhu; Chen, Qinghua; Feng, Shasha; Sun, Yan; Zhang, Qingyou; Tang, Chaoshu; Du, Junbao; Jin, Hongfang
Abstract : Background . The study aimed to investigate whether endogenous H2 S pathway was involved in high-salt-stimulated mitochondria-related vascular endothelial cell (VEC) apoptosis. Methods . Cultured human umbilical vein endothelial cells (HUVECs) were used in the study. H2 S content in the supernatant was detected. Western blot was used to detect expression of cystathionine gamma-lyase (CSE), cleaved-caspase-3, and mitochondrial and cytosolic cytochrome c (cytc). Fluorescent probes were used to quantitatively detect superoxide anion generation and measure the in situ superoxide anion generation in HUVEC. Mitochondrial membrane pore opening, mitochondrial membrane potential, and caspase-9 activities were measured. The cell apoptosis was detected by cell death ELISA and TdT-mediated dUTP nick end labeling (TUNEL) methods. Results . High-salt treatment downregulated the endogenous VEC H2 S/CSE pathway, in association with increased generation of oxygen free radicals, decreased mitochondrial membrane potential, enhanced the opening of mitochondrial membrane permeability transition pore and leakage of mitochondrial cytc, activated cytoplasmic caspase-9 and caspase-3 and subsequently induced VEC apoptosis. However, supplementation of H2 S donor markedly inhibited VEC oxidative stress and mitochondria-related VEC apoptosis induced by high salt. Conclusion . H2 S/CSE pathway is an important endogenous defensive system in endothelial cells antagonizing high-salt insult. The protective mechanisms for VEC damage might involve inhibiting oxidative stress and protecting mitochondrial injury.